2018
DOI: 10.1097/eja.0000000000000867
|View full text |Cite
|
Sign up to set email alerts
|

Emergence delirium in children is related to epileptiform discharges during anaesthesia induction

Abstract: NCT02481999.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 25 publications
2
21
0
2
Order By: Relevance
“…The occurrence of Burst Suppression during general anaesthesia in elderly patients is positively correlated to the incidence of postoperative delirium, hence one might propose that elderly patients struggle to restore the preoperative brain metabolism level. In contrast, in children neuronal hyperexcitability – as seen by occurrence of interictal, epileptiform discharges during anaesthesia induction or increased frontal connectivity during emergence of general anaesthesia – has been related to ED [7, 8]. These striking differences in EEG activity related to delirium in children compared with elderly patients extends into its clinical presentation, where delirious children present with crying, agitation, disorientation and altered response to their surroundings, whereas elderly patients present primarily with a hypoactive form of delirium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of Burst Suppression during general anaesthesia in elderly patients is positively correlated to the incidence of postoperative delirium, hence one might propose that elderly patients struggle to restore the preoperative brain metabolism level. In contrast, in children neuronal hyperexcitability – as seen by occurrence of interictal, epileptiform discharges during anaesthesia induction or increased frontal connectivity during emergence of general anaesthesia – has been related to ED [7, 8]. These striking differences in EEG activity related to delirium in children compared with elderly patients extends into its clinical presentation, where delirious children present with crying, agitation, disorientation and altered response to their surroundings, whereas elderly patients present primarily with a hypoactive form of delirium.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated concentrations of the anaesthetic agent sevoflurane cause an increase of epileptiform discharges during anaesthesia induction in children [6]. In a former EEG analysis - focusing on the period of anaesthesia induction in the same patient cohort that is presented here - we have shown that the occurrence of interictal, epileptiform discharges is positively related to the development of ED [7]. In a study from Martin and colleagues analysing multichannel EEG characteristics in 12 children, from whom 5 developed ED, ED was associated with arousal from an indeterminate state (low voltage / fast frequency EEG activity) and an increased frontal cortical functional connectivity [8].…”
Section: Introductionmentioning
confidence: 99%
“…In children elevated concentrations of the anaesthetic agent Sevoflurane cause an increase of epileptiform discharges during anaesthesia induction (6). In a former EEG analysis -focusing on the period of anaesthesia induction in the same patients group presented here -we had shown that the occurrence of interictal, epileptiform discharges, is positively related to the development of ED (7). In a study from Martin and colleagues, analyzing multichannel EEG characteristics in 12 children, from whom 5 developed ED, ED was associated with arousal from an indeterminate state (low voltage / fast frequency EEG activity) and an increased frontal cortical functional connectivity (8).…”
Section: Introductionmentioning
confidence: 58%
“…The occurrence of Burst Suppression during general anaesthesia in elderly patients is positively correlated to the incidence of postoperative delirium, hence one might propose, that elderly patients struggle to restore preoperative brain metabolism level. In contrast, in children neuronal hyperexcitability -as seen by occurrence of interictal, epileptiform discharges during anaesthesia induction or increased frontal connectivity during emergence of general anaesthesia -has been related to ED (7,8). These striking differences in EEG activity related to delirium in children compared with elderly patients extends into its clinical presentation, where delirious children present with crying, agitation, disorientation and altered response to their surroundings, whereas elderly patients present primarily with a hypoactive form of delirium.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that these paradoxical discharges found in children with or without epilepsy are related to poorer cognitive performance [8] and emergency delirium. [9] However, the incidence, prevention and risk factors of these epileptiform patterns during sevoflurane anesthesia in children are still under debate. Based on the above facts and the existing studies, it is urgent to conduct this systematic review and meta-analysis to evaluate the epileptic potential of sevoflurane in EEG during general anesthesia in children.…”
Section: Introductionmentioning
confidence: 99%